2016
DOI: 10.1136/jclinpath-2016-203984
|View full text |Cite
|
Sign up to set email alerts
|

A historical perspective on crush syndrome: the clinical application of its pathogenesis, established by the study of wartime crush injuries

Abstract: Crush syndrome is a fine example of how pathology can play a direct role in revealing the best treatment and management for diseases. It can occur when crush injuries are sustained. Skeletal muscle becomes damaged under the weight of a heavy object, and victims experience severe shock and renal failure. The discovery of the pathology of crush syndrome belongs to two individuals: Seigo Minami and Eric Bywaters. They separately helped to define the pathogenesis of crush syndrome during World Wars I and II. Seigo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 10 publications
0
23
0
6
Order By: Relevance
“…When comparing the main findings of our review with this literature, we identified some similar patterns. Both compartment syndrome, crush syndrome, and vascular injury were characterized by ischemia–reperfusion injury . Compartment syndrome and crush syndrome are to a major degree associated with elevated interstitial pressure, and more specifically intracompartmental pressure, as a consequence of edema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing the main findings of our review with this literature, we identified some similar patterns. Both compartment syndrome, crush syndrome, and vascular injury were characterized by ischemia–reperfusion injury . Compartment syndrome and crush syndrome are to a major degree associated with elevated interstitial pressure, and more specifically intracompartmental pressure, as a consequence of edema.…”
Section: Discussionmentioning
confidence: 99%
“…Both compartment syndrome, crush syndrome, and vascular injury were characterized by ischemia-reperfusion injury. [86][87][88] Compartment syndrome and crush syndrome are to a major degree associated with elevated interstitial pressure, and more specifically intracompartmental pressure, as a consequence of edema. Moreover, in all four conditions, neutrophils are the first invading inflammatory cells, followed by macrophages, and promote further muscle damage.…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is the most common complication of rhabdomyolysis in crush syndrome, and it is an important factor that causes death and poor prognosis in patients. 3 Abbreviations: AKI: acute kidney injury BUN: blood urea nitrogen ELISA: enzyme-linked immunosorbent assay HE: Haematoxylin and Eosin stain IL-6: interleukin-6 JNK: c-Jun N-terminal kinase Mb: myoglobin mRNA: messenger ribonucleic acid NF-κB: nuclear factor-kappa B PCR: polymerase chain reaction TBS: tris-buffered saline TLR: toll-like receptor TNF-α: tumor necrosis factor-α Toll-like receptors (TLRs) are the members of the membrane protein family which can identify pathogen-associated molecules and mediate innate immune response; 4 TLR4 is an important member of the TLRs receptor family and belongs to I transmembrane receptor. Binding of stimulating factors to the TLR4 receptor is the first step in activating the innate immune system.…”
Section: Introductionmentioning
confidence: 99%
“…6 8 As a result of I/R injury (especially in the lower extremities, which contain a large amount of skeletal muscle), serious systemic conditions including the acute renal failure can be caused by secreted chemical mediators derived from ischemic skeletal muscles, as represented by crush syndrome. 3,7…”
Section: Introductionmentioning
confidence: 99%